2013
DOI: 10.1186/1471-2229-13-27
|View full text |Cite
|
Sign up to set email alerts
|

Ginger and turmeric expressed sequence tags identify signature genes for rhizome identity and development and the biosynthesis of curcuminoids, gingerols and terpenoids

Abstract: BackgroundGinger (Zingiber officinale) and turmeric (Curcuma longa) accumulate important pharmacologically active metabolites at high levels in their rhizomes. Despite their importance, relatively little is known regarding gene expression in the rhizomes of ginger and turmeric.ResultsIn order to identify rhizome-enriched genes and genes encoding specialized metabolism enzymes and pathway regulators, we evaluated an assembled collection of expressed sequence tags (ESTs) from eight different ginger and turmeric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 87 publications
(93 reference statements)
1
34
1
Order By: Relevance
“…Except MADS-box gene, this was the first report that BDP, LOB, ROP, WOX4, ULT1, KNOX, LHW, CLE, and C3CH4 genes expressed highly in rhizome (Jang et al 2006;Koo et al 2013). To date, although whether the above genes were involved with the rhizome formation and development have not been identified by transgenic evidence, those highly expressing level in rhizome indicated that they might play essential role in the rhizome formation and development.…”
Section: Discussionmentioning
confidence: 86%
“…Except MADS-box gene, this was the first report that BDP, LOB, ROP, WOX4, ULT1, KNOX, LHW, CLE, and C3CH4 genes expressed highly in rhizome (Jang et al 2006;Koo et al 2013). To date, although whether the above genes were involved with the rhizome formation and development have not been identified by transgenic evidence, those highly expressing level in rhizome indicated that they might play essential role in the rhizome formation and development.…”
Section: Discussionmentioning
confidence: 86%
“…Within this experiment, the authors found that rhizome formation was a key but not the only factor that controlled winter survival, again providing indirect evidence that many aspects of dormancy and winter-survival can be separated. More recently, other researchers have begun the task of dissecting the genes and co-expressed gene sets that might control rhizomatousness in monocots [85][86][87][88][89]. These studies have identified transcripts for several genes including transcription factors that are selectively enriched in rhizomes relative to shoots.…”
Section: Molecular Studies On Rhizomatousness In Grassesmentioning
confidence: 99%
“…In addition, we referred to the Aromatic Rhizome EST database in the University of Arizona (http://www.agcol. arizona.edu/cgi-bin/pave/GT/index.cgi, (Koo et al 2013)), because this database was opened before we constructed our own database from cv. Kintoki.…”
Section: Isolation Of Gedh Cdna and Expression In E Colimentioning
confidence: 99%
“…Our previous report showed that NADP + -dependent ADH activity for geraniol was involved in production of citral, whereas geraniol oxidase showed no activity (Sekiwa- Iijima et al 2001). Therefore, we screened candidate GeDH cDNA using the EST database established by the University of Arizona (Koo et al 2013) and our domestic sequence collections constructed for Z. officinale cv. Kintoki using next-generation sequencing technology.…”
Section: Cloning and Phylogenetic Analysis Of Gedhmentioning
confidence: 99%